BIBLIOMETRIC ANALYSIS OF INFLUENCER PERSONAL BRANDING RESEARCH IN MARKETING MANAGEMENT: TRENDS, THEMES, AND DEVELOPMENTS - Shinta Kartikasari; Adiba Fuad Syamlan; Umar Burhan (STMIK Indonesia Banda Aceh, 2026)
The phenomenon of influencer personal branding has developed into a central strategy in digital marketing management , but systematic academic mapping of its research development is still very limited . Objective: This study aims to map trends , dominant themes , intellectual structures , and collaborative networks of influencer personal branding research in marketing management using bibliometric analysis . Method: Quantitative analysis was conducted on 312 publications from the Scopus database for the period 2021–2025 using VOSviewer software for keyword network visualization , co- author analysis , and thematic cluster mapping . Results: The average publication growth was 26.7 percent per year with an R - squared value of 0.91. Four theme clusters were identified, namely influencer marketing, sustainable fashion, social media ecosystems, and authenticity and psychological values. The United States dominated publications with 28.6 percent, while Indonesia only contributed 2.1 percent. Conclusion: There are research gaps in the dimensions of micro-influencers, metaverse technology, business actor perspectives, and cross-cultural studies that need to be prioritized in future research agendas.